10(v+4)-2v=4(2v+2)-16

Simple and best practice solution for 10(v+4)-2v=4(2v+2)-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(v+4)-2v=4(2v+2)-16 equation:


Simplifying
10(v + 4) + -2v = 4(2v + 2) + -16

Reorder the terms:
10(4 + v) + -2v = 4(2v + 2) + -16
(4 * 10 + v * 10) + -2v = 4(2v + 2) + -16
(40 + 10v) + -2v = 4(2v + 2) + -16

Combine like terms: 10v + -2v = 8v
40 + 8v = 4(2v + 2) + -16

Reorder the terms:
40 + 8v = 4(2 + 2v) + -16
40 + 8v = (2 * 4 + 2v * 4) + -16
40 + 8v = (8 + 8v) + -16

Reorder the terms:
40 + 8v = 8 + -16 + 8v

Combine like terms: 8 + -16 = -8
40 + 8v = -8 + 8v

Add '-8v' to each side of the equation.
40 + 8v + -8v = -8 + 8v + -8v

Combine like terms: 8v + -8v = 0
40 + 0 = -8 + 8v + -8v
40 = -8 + 8v + -8v

Combine like terms: 8v + -8v = 0
40 = -8 + 0
40 = -8

Solving
40 = -8

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| p=2(12)+2(54) | | 92.7*14.2= | | q^3/3 | | 0=-2n | | 5(3x-6)-3(x+3)-15x= | | -8(v+4)+3v+5=5v+7 | | (-8x^3/y^-8)^(2/3) | | 56=6(X) | | 5-(t+3)=-1+2(t-5) | | 5w-3(4x-2w)+3x= | | A=1/2(4.5*h) | | 5(3x-7)-4(x+1)-16x= | | X-7/3 | | 6v-14=3v+7 | | -9+10x= | | .25n+1n=9.8 | | 2x-3=1-x | | 0=x^2-8+3 | | 3xy+4yx= | | 3/2*x=12 | | -8-5x= | | -9+2p= | | x+9=-26 | | (4x-24)+(3x+18)= | | 8x+2x=-10 | | 486=18y+18 | | 17+x+8+x=13 | | 3x-(4x+1)=2x-7 | | 48=4b-8 | | 2(-3a+5)=-4(9+4) | | n^2-6n-4n=0 | | 2k+7c+5c-k= |

Equations solver categories